OUTCOMES OF LAPAROSCOPIC SURGERY FOR OVARIAN TUMORS AT PHU THO OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of laparoscopic management of ovarian tumors at Phu Tho Obstetrics and Pediatrics Hospital from January 2023 to December 2024.Methods: A retrospective cross-sectional descriptive study was conducted on 189 patients diagnosed with ovarian tumors who underwent laparoscopic surgery between January 1, 2023, and December 31, 2024.Results: The majority of patients underwent ovarian cystectomy (65.6%). The rate of ovarian-sparing cystectomy among patients under 45 years of age was significantly high (81.8%). In the premenopausal group, ovarian-sparing cystectomy accounted for the majority of cases at 75.2%. Regarding histopathology, for dermoid cysts (mature cystic teratomas), cystectomy was the predominant method (82%), while oophorectomy accounted for only 18%. Tumor size significantly influenced the surgical approach: for tumors smaller than 5 cm, the cystectomy rate was 77.9%; whereas for tumors larger than 10 cm, this rate decreased to 42.9%.Conclusion: The rate of ovarian-sparing cystectomy is high among patients of reproductive age and those with benign histopathology.
Keywords: Ovarian tumor, dermoid cyst, ovarian-sparing cystectomy.